2009
DOI: 10.1080/03630240903424020
|View full text |Cite
|
Sign up to set email alerts
|

Women Bound to Be Active: One Year Follow-Up to an Innovative Pilot Intervention to Increase Physical Activity and Self-Worth in Women

Abstract: The purpose of this investigation was to assess the effectiveness of a lifestyle intervention (a women's book club; Women Bound to be Active) in promoting long-term physical activity (PA). Thirty-five women (26-70 years; mean age 50.6 years) completed the 8-month intervention and participated in the one-year follow-up. At follow-up, PA returned to baseline levels; however, self-worth and body mass index significantly improved. Women were more knowledgeable about PA at follow-up; however, they failed to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Based on the tenets of Social Cognitive Theory (SCT) and self-worth, [6][7][8] Fit Minded utilizes books as a platform for group discussion of SCT constructs and self-worth related to PA (e.g., goal setting, barriers to PA, PA awareness/perceptions, quality of life). Despite participants demonstrating short-and longterm improvements in PA, 44% of women in one book club did not complete the program, citing time and other commitments as barriers to their participation in the program and PA. 2,3,5 This level of attrition is consistent with face-to-face programs in which half of participants often drop out within 3-6 months because of factors such as time, cost, and transportation. 9,10 Internet-based delivery of the book club program may help to mitigate barriers to participation in the face-toface program, such as time, childcare, travel to program sites, and residing outside the local area.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Based on the tenets of Social Cognitive Theory (SCT) and self-worth, [6][7][8] Fit Minded utilizes books as a platform for group discussion of SCT constructs and self-worth related to PA (e.g., goal setting, barriers to PA, PA awareness/perceptions, quality of life). Despite participants demonstrating short-and longterm improvements in PA, 44% of women in one book club did not complete the program, citing time and other commitments as barriers to their participation in the program and PA. 2,3,5 This level of attrition is consistent with face-to-face programs in which half of participants often drop out within 3-6 months because of factors such as time, cost, and transportation. 9,10 Internet-based delivery of the book club program may help to mitigate barriers to participation in the face-toface program, such as time, childcare, travel to program sites, and residing outside the local area.…”
Section: Introductionsupporting
confidence: 53%
“…[2][3][4][5] In brief, Fit Minded targets lifestyle PA using popular, best-selling books (selfhelp, memoirs) as platforms for weekly, group-based discussion targeting SCT constructs and self-worth in a progressive manner. Books are selected for their relevance to social cognitive behavioral strategies (i.e., self-efficacy, self-regulation, PA benefits/barriers, social support), self-worth, and PA, their applicability to womenspecific issues, and their ratings by women from previous book clubs.…”
Section: Intervention Content and Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…20 In a 1-year follow-up to the first pilot study, women reported significant improvements in their self-worth and body mass index as compared with baseline. 21 PA levels, however, varied among participants at the 1-year follow-up. Although some women reported challenges to maintaining PA, at 1-year follow-up women remained more knowledgeable about PA and had developed strategies to overcome barriers as compared with baseline.…”
mentioning
confidence: 99%
“…Nevertheless, women reported ongoing barriers to PA which included 1) decreased social support at the end of the intervention, 2) competing time between PA and work/ family obligations, and 3) lack of motivation. 21 More studies are needed that explore in-depth reasons women are able (or unable) to maintain PA 1 year after participation in a PA program. Ideal approaches to increasing longterm adherence in women remain unclear, 5 and further longitudinal research utilizing mixed-methods techniques should explore correlates of women's PA adherence.…”
mentioning
confidence: 99%